Manual of Thoracic Endoaortic Surgery - Kpodonu, Jacques. (Springer London : Imprint: Springer, 2010)
The development of less invasive technologies has resulted in a changing paradigm for the management of aortic diseases. Endovascular and hybrid surgical approaches have gradually been adopted by cardiovascular surgeons and have proven to shorten hospitalization, reduce morbidity and mortality, speed recovery and hasten return to normal life, and consequently have shown to be favorable to open surgical techniques in most situations. Nevertheless, the current training programs have not been designed to accommodate the rapid evolution in endovascular technology, 3D imaging modalities, intravascular ultrasound technology and advanced navigational tools. It is essential that cardiovascular surgeons have the fundamental knowledge and skill sets required to understand and incorporate all these latest technology into the practice of aortic surgery. The Manual of Thoracic Endoaortic Surgery identifies both the limitations and the advantages of thoracic aortic endografting techniques. While there is no substitute for learning from experience, the book provides a useful tool for practitioners as they plan and execute treatment plans for patients with these various thoracic aortic pathologies as well as serving as a useful reference as this segment of the field expands.